Тенденції та перспективи розвитку брендингу в умовах євроінтеграційних процесів в Україні - Горбаль, Н. І.; Окань, Л. Ю.; Романишин, С. Б. (Видавництво Львівської політехніки, 2015)
Розглянуто сутність та значення бренду, особливості брендингу. Досліджено провідні бренди світу та тенденції розвитку брендингу. Проаналізовано основні тенденції розвитку вітчизняного брендингу, особливості та проблеми специфіки застосування брендингу в Україні. Виділено провідні бренди України та тенденції щодо створення сильних брендів українських компаній. Наголошено на важливості брендингу для вітчизняних підприємств в умовах євроінтеграції. Узагальнено ключові міжнародні нормативні акти щодо торговельних марок, зокрема особливості їх реєстрації за кордоном. Висвітлено особливості й переваги для українських підприємств реєстрації марок за Системою охорони торгових марок ЄС. Наголошено на необхідності й проблемах імплементації Україною стандартів ЄС щодо прав інтелектуальної власності. The article examines the nature and role of the brand, branding features and specific. The investigation of the world’s leading brands and branding trends is provided. The basic trends of national branding, features, problems and specific of branding in Ukraine are shown. Ukrainian leading brands and trends of creating strong brands by Ukrainian companies are depicted. The importance of branding for domestic enterprises in the terms of European integration is emphasized. Key international regulations concerning trademarks, including their registration abroad are overviewed. The specific features and advantages for Ukrainian companies of trademarks registration by the EU Community marks system are highlighted. The necessity and problems of implementation of the EU standards on intellectual property rights by Ukraine is stressed. Branding is a systematic, reasonable, balanced process that involves planning and implementation of marketing measures to create a brand, the development of a plan for the transformation of the trade mark into the brand, particularly through the development of an appropriate name, corporate style and design, advertising campaigns, actions to stimulate sales, targeted PR, in order to form the desired associative consumers’ experience. The development of the company’s brand increases the demand for products and its competitiveness, creates awareness among consumers, enhances the company's image, which in turn increases its value. World experience shows that introduction and use of branding by modern enterprises is one of the strategic goals that provides revenue enhancement, increases assets and a value of companies. Today brand is an important element of a company’s assets. However, for most Ukrainian companies branding technologies are still new and unexplored. According to the BrandZ company, which annually conducts studies to determine world’s 100 most valuable brands, the top ten brands during six months of 2015 were: Apple (brand value is 246.99 bln.USD), Google (173,65 bln.USD), Microsoft (115,5 bln.USD), IBM (93,99 bln.USD), Visa (91,96 bln.USD), At&t (89,49 bln.USD) Verizon (86,01 bln.USD), Coca- Cola (83,84 bln.USD), McDonald's (85,7 bln.USD), Marlboro (80,35 bln.USD). Total value of brands in comparison with 2014 has increased by 14%, ensuring companies’ high profitability. Dynamic changes in the brands value in recent years indicate continued development of companies and investments in branding. The most successful European brands in 2014 were: IKEA (brand value is 11.5 bln.USD), Nestle (11.8 bln.USD), Gucci (12.1 bln.USD), Siemens (13.7 bln.USD), HSBC (15.2 bln.USD), L'Oreal (16.9 bln.USD), SAP (19.6 bln.USD), Mercedes-Benz (23.5 bln.USD), BMW (27,9 bln.USD), Louis Vuitton (28 bln.USD). During the last 10 years European brands lost their positions to Chinese companies that have rapidly captured worldwide telecommunications and technology markets. According to the European statistical company development of branding in EU is concentrated mainly in the fields of finances, technology and food industry. Analyzing trends of Ukrainian branding, it should be noted that in the last decade there has been intensification of investments in brand development by the largest companies. Main feature of Ukrainian branding is that companies that are focused on building strong brands, are constantly modifying their products in accordance to the latest innovations, improving products, expanding the product range. National branding development is particularly important in the context of Euro integration processes, which are implemented nowadays and promote both political and economic relations’ improvement between the EU and Ukraine. This will help to expand market shares of Ukrainian manufacturers at the “western market”. In such conditions branding is a key tool in the promotion of domestic products, because with its help Ukrainian producers can quickly adapt to new markets.
Tendencies and prospects of branding development in the conditions of eurointegration processes in Ukraine
Keywords: бренд; брендинг; торгівельна марка; просування товару; конкуренція; євроінтеграція; ринки збуту; brand; branding; trademark; sales promotion; competition; European integration; markets